Human Rights Theory - Cingranelli, David. author. aut Link
XII, 258 p.
Keywords: This study attempts to facilitate the development of empirical theories relevant to human rights phenomena. It is designed to be of use to policymakers regarding appropriate strategies for measuring human rights practices and for evaluating human rights policies.